Lymphatic Alterations Under Tattoos: Preliminary Reports of One Observational Study - Bourgeois P; Roman MM; Schweicher J; Lavoisier P; Maquet P; Karler C; Lizewski M; Fouarge A; Cuylits N; del Marmol V; Leduc O (Dove Medical Press, 2023)
Pierre Bourgeois,1- 4 Mirela Mariana Roman,5 Justine Schweicher,6 Pauline Lavoisier,6 Philippe Maquet,6 Clarence Karler,7 Mateusz Lizewski,8 Alessandro Fouarge,8 Nicolas Cuylits,8 Véronique del Marmol,1 Olivier Leduc6 1Service of Dermatology, Hospital Erasme, Université Libre de Bruxelles, Brussels, Belgium; 2Services of Nuclear Medicine, HIS-IZZ Hospitals, Université Libre de Bruxelles, Brussels, Belgium; 3Multi-Disciplinary Clinic of Lymphology, Institute Jules Bordet, Université Libre de Bruxelles, Brussels, Belgium; 4Service of Vascular Surgery, HIS-IZZ Hospitals, Université Libre de Bruxelles, Brussels, Belgium; 5Department of Mammo-Pelvic Surgery, Institute Jules Bordet, Université Libre de Bruxelles, Brussels, Belgium; 6Unité de lympho-phlébologie, Haute Ecole Bruxelles-Brabant, Haute Ecole Robert Schuman, Brussels, Belgium; 7Department of Anesthesia-Algologia, Hospital Moliere, Université Libre de Bruxelles, Brussels, Belgium; 8Service of Plastic, Reconstructive and Aesthetic Surgery, Hospital Erasme, Université Libre de Bruxelles, Brussels, BelgiumCorrespondence: Pierre Bourgeois, Department of Dermatology, University Hospital Erasme, Université Libre de Bruxelles, 808, route de Lennik, Brussels, 1070, Belgium, Tel +32495201906, Email pierre.bourgeois@erasme.ulb.ac.beBackground: The number of people within the European population having at least one tattoo has increased notably and with it the number of tattoo-associated clinical complications. The injected inks are known to be removed by the lymphatic vessels and can be found in the draining lymph nodes.Aim of the Study: To report our observations on the lymphatic drainages seen under tattoos using near infrared fluorescence imaging of these lymphatic vessels after the injection of indocyanine green.Material and Methods: Indocyanine green was injected intradermally at the basis of the 20 tattooed area(s) in 19 subjects (nine women and ten men; mean age = 28.6). Ten subjects had only black tattoos (six upper limbs and four lower limbs), five (two upper limbs and three lower limbs) black and white tattoos and five multi-colored tattooed limbs (four lower limbs and one upper limb).Results: The imaging exams revealed alterations in eight individuals, seven of whom had tattoos on their lower limbs. Furthermore, the imaging results showed that the abnormalities might be related to the tattooed limb, the tattoo extent and colour.Conclusion: Alterations of the cutaneous lymphatic channels are frequently observed under tattooed territories. Their causal factors should be more precisely studied in future works and these lymphatic alterations should be considered in tattooed patients when using similar imaging techniques for therapeutic and surgical assessments.Keywords: tattoo, near infra-red fluorescence lymphatic imaging, indocyanine green, lymphatic, lymph vessel